2002
DOI: 10.5488/cmp.5.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Star Polymers: From Conformations to Interactions to Phase Diagrams

Abstract: We review recent progress achieved in the theoretical description of the interactions, correlations, and phase behavior of concentrated solutions of star polymers, sterically stabilized colloids, and micelles. We show that the theoretical prediction of an ultrasoft, logarithmically diverging effective interaction between the star centers, which has been confirmed by SANSexperiments and computer simulations, lies in the core of a host of unusual phenomena encountered in such systems. These include anomalous str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 99 publications
2
31
1
1
Order By: Relevance
“…The functionality-dependent bcc-and fcc-solids [17,18], as well as the reentrant melting transition [19], have been experimentally observed in solutions of star-like block copolymer micelles. A second freezing transition observed in the same experiments can be interpreted as the freezing in a bco crystal [20].…”
Section: Introductionmentioning
confidence: 57%
“…The functionality-dependent bcc-and fcc-solids [17,18], as well as the reentrant melting transition [19], have been experimentally observed in solutions of star-like block copolymer micelles. A second freezing transition observed in the same experiments can be interpreted as the freezing in a bco crystal [20].…”
Section: Introductionmentioning
confidence: 57%
“…We observed that the addition of hydroxylsubstituted anthracene molecules increases the rigidity of PS-b-P4VP micelles and promotes hexagonal order 119 . Rigid micelles could have a behavior closer to star copolymers 120 or hairy nanoparticles with inorganic core 121,122 , but in opposite to those, they would still be able to deform or fuse, if the thermodynamic conditions allow it. By immersion in water a fast solvent exchange takes place, particularly in the layer close to the solution-water interface, leading to abrupt changes in the thermodynamic conditions with consequent gelation and kinetic trapping of the self-assembly morphology.…”
Section: Snips Processmentioning
confidence: 99%
“…Such soft potentials arise as the effective interaction potential between polymers or soft macromolecules in solution [25][26][27][28][29][30][31][32][33][34][35][36][37]. Our main reason for considering this model centres on the fact that the structure and phase behaviour (i.e.…”
Section: Model Fluidmentioning
confidence: 99%